Mystus catapogon, a new catfish (Siluriformes: Bagridae) species from Kerala, India - Plamoottil, Mathews (Journal of Research in Biology, 2016)
Mystus catapogon, a new fish species, is distinguished from its congeners by the following combination of characters: maxillary barbels reach beyond caudal fin base; outer mandibulars reach to base of ventral fin and inner mandibular barbels to middle of pectoral fin; Snout shorter; cephalic groove long, shallow and divided into two fontanels and reaching occipital process; occipital process does not reach basal bone of dorsal fin; adipose fin located fairly behind the rayed dorsal fin; body without any mid lateral stripe. The new fish is described and compared with its congeners.